Simultaneous Two-Vessel Subacute Stent Thrombosis Caused by Clopidogrel Resistance from CYP2C19 Polymorphism. (31st July 2016) - Afzal, Ashwad; Patel, Bimal; Patel, Neel; Sattur, Sudhakar; Patel, Vinod
Abstract : Clopidogrel resistance from CYP2C19 polymorphism has been associated with stent thrombosis in patients undergoing percutaneous coronary intervention with drug-eluting stents. We present a case of a 76-year-old male who received drug-eluting stents to the right coronary artery and left anterior descending artery for non-ST elevation myocardial infarction and was discharged on dual antiplatelet therapy with aspirin and clopidogrel. He subsequently presented with chest pain from anterior, anteroseptal, and inferior ST segment elevation myocardial infarction. An emergent coronary angiogram revealed acute stent thrombosis with 100% occlusion of RCA and LAD that was successfully treated with thrombus aspiration and angioplasty. Although he was compliant with his dual antiplatelet therapy, he developed stent thrombosis, which was confirmed as clopidogrel resistance from homozygous CYP2C19 polymorphism.